Determinants of Competitive Advantage and Their Impact on Consumer Satisfaction at Chicken Restaurants in South Jakarta - Digdowiseiso, Kumba; Lestari, Rahayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Changes in consumer behavior through the appetite of the younger generation, lifestyle, digital technology make producers and marketers start thinking about using a superior marketing strategy among their competitors. Increased sales will be achieved if it can create a competitive advantage among chicken restaurants. This study aims to analyze the effects of market orientation and product innovation on competitive advantage and customer satisfaction. It also investigates the effect of competitive advantage on customer satisfaction. The study was conducted on 150 culinary SMEs (Small-Medium Enterprises) of the Chicken Restaurant in the South Jakarta area. The primary data obtained from interviews with completeness in the form of a questionnaire. While, secondary data is collected from information on SMEs and the internet. We utilized the Structural Equation Modeling (SEM) method with the help of LISREL 8.70 software. Our result found that both market orientation and product innovation together produced a significant effect on competitive advantage. We also found that market orientation, product innovation, and competitive advantage together affected customer satisfaction.